The Impact of Social Media Marketing on Small Natural Cosmetic Brands - Iasmina-Iulia GRADINESCU; Andreea RADULIAN; Olguta Anca ORZAN (Communications of International Proceedings, 2021)
This study focuses on analysing the effects of social media on small natural dermo-cosmetic brands. Moreover, the research takes into consideration the possible implications of social proof strategy when it comes to consumers’ purchasing patterns. In other words, this study aims to assess whether or not informational social influence can generate a shift concerning consumer buying habits. Social media revolution has changed how traditional communication, as well as marketing communication, is conducted, subsequently leading to new forms of interactions for the acquisition of goods and services. The adjustments that took place concerning the consumptive patterns of media incentivised companies not only to shift their focus from products to people but also from information delivery to information exchange. With this new marketing communication in place, new challenges and opportunities are present anywhere, social media interaction becoming the driver of the purchase decision and the trigger of awareness for both brands and products. The study field of the research is represented by a Romanian small natural dermo-cosmetic brand, Careless Beauty. To conduct the analysis, a questionnaire was delivered to both males and females 18 years of age and above. The survey in question consists of six main variables: natural dermo-cosmetics general perception, purchase intention, followers, reviews, celebrity endorsement and last but not least, social community recommendation. All these variables are being used throughout four regressions to analyse the relationships between social proof strategy components and an individual’s purchase intention.
Keywords: Social Media; Social Proof; Purchase Intention; Natural Dermo-Cosmetics